The mathematics of Egypt, Mesopotamia, China, India, and Islam a sourcebook - Katz, Victor J.; Imhausen, Annette; Robson, Eleanor; Dauben, Joseph; Plofker, Kim; Berggren, J.Lennart (Princeton University Press, 2007)
Provides a collection of English translations of mathematical texts from five important ancient and medieval non-Western mathematical cultures, and puts them into historical and mathematical context. This book is intended for mathematics teachers who want to use non-Western mathematical ideas in the classroom